Volunteer management and institutional performance: Developing amil competencies for enhanced effectiveness in Islamic social finance organizations - Marfu'ah, Usfiyatul; Zainurrakhmah, Zainurrakhmah; Sahasti, Julananda Putri; Safitri, Ani (Jurnal Ilmu Dakwah, 2025)
Purpose - The purpose of this study was to examine the ability of Amil volunteers in the collection and distribution of ZIS funds, and to reveal the differences in position between Amil volunteers and Amil Method – This research uses a descriptive qualitative method. Primary data were obtained through focus group discussions (FGDs) and in-depth interviews involving 15 Amil volunteers at LAZISNU Semarang City, while secondary data were obtained from several sources, both from journal articles, official websites of zakat; infaq; and shadaqah management institutions, ministry of religion websites, and online news that have relevance to the research theme. Result  –  The results showed that the potential of Amil volunteers in collecting and distributing ZIS funds is minimal. There are more Amil volunteers than Amil, but they lack adequate skills. In addition, there is a gap between Amil and Amil volunteers. The gap can be observed in the recognition, the knowledge of ZIS materials, or the capacity to manage ZIS Implication – The results of this study are expected to contribute to increasing the effectiveness and efficiency of ZIS human resource management, especially for ZIS volunteers Originality/Value – This research is the first study explaining ZIS volunteers, so it has high originality. Originality is seen in the primary focus of the study, human resources in Islamic organizations, which are not widely highlighted in research studies. *** Tujuan - Tujuan penelitian ini adalah untuk mengkaji kemampuan relawan Amil dalam pengumpulan dan pendistribusian dana ZIS, serta mengidentifikasi perbedaan peran antara relawan Amil dan Amil Metode – Penelitian ini menggunakan metode kualitatif deskriptif. Data primer diperoleh melalui diskusi kelompok terfokus (FGD) dan wawancara mendalam dengan 15 relawan Amil di LAZISNU Kota Semarang, sementara data sekunder diperoleh dari berbagai sumber, termasuk artikel jurnal, situs web resmi lembaga pengelolaan zakat, infaq, dan shadaqah, situs web Kementerian Agama, serta berita online yang relevan dengan tema penelitian. Hasil – Hasil penelitian menunjukkan bahwa potensi relawan Amil dalam mengumpulkan dan mendistribusikan dana ZIS sangat minim. Jumlah relawan Amil lebih banyak daripada Amil, namun mereka kurang memiliki keterampilan yang memadai. Selain itu, terdapat kesenjangan antara Amil dan relawan Amil. Kesenjangan tersebut dapat diamati dalam hal pengakuan, pengetahuan tentang materi ZIS, atau kemampuan mengelola ZIS Implikasi – Hasil penelitian ini diharapkan dapat berkontribusi pada peningkatan efektivitas dan efisiensi manajemen sumber daya manusia ZIS, terutama untuk relawan ZIS. Orisinalitas/Nilai – Penelitian ini merupakan studi pertama yang menjelaskan relawan ZIS, sehingga memiliki keaslian yang tinggi. Keaslian terlihat pada fokus utama penelitian, yaitu sumber daya manusia dalam organisasi Islam, yang belum banyak ditekankan dalam penelitian-penelitian sebelumnya.